Genome-Wide Identification and Expression Analysis of the LbDof Transcription Factor Family Genes in Lycium barbarum - Yuchang Wang; Hongrui Wang; Weinan Li; Guoli Dai; Jinhuan Chen (Plants)
Lycium barbarum, a nutrient-rich fruit known for its resilience to drought and high salinity, presents an opportunity to explore stress tolerance at the molecular level. This study explores the molecular mechanisms underlying stress tolerance and fruit development in L. barbarum by characterizing its Dof transcription factor family. Through genomic analysis, 39 LbDof genes were identified, with their structural, phylogenetic, and physicochemical properties systematically examined. Cis-acting regulatory element analysis revealed motifs associated with growth, stress, light, and hormone responses, while expression profiling demonstrated organ-specific patterns and significant upregulation under drought and saline–alkaline stress. Additionally, dynamic expression changes were observed across fruit development stages, suggesting regulatory roles in maturation. Phylogenetic classification grouped LbDof genes into ten subgroups, with chromosomal mapping indicating segmental duplications as a key evolutionary driver. Furthermore, the study offers a comprehensive genomic and functional analysis of LbDof genes, highlighting their potential roles in stress adaptation and fruit maturation. The findings provide a theoretical basis for breeding stress-resistant crops and insights into enhancing plant resilience.